The Post-Anaesthesia N-acetylcysteine Cognitive Evaluation (PANACEA) trial: study protocol for a randomised controlled trial. Issue 1 (December 2016) - Skvarc, David; Dean, Olivia; Byrne, Linda; Gray, Laura; Ives, Kathryn; Lane, Stephen; Lewis, Matthew; Osborne, Cameron; Page, Richard; Stupart, Douglas; Turner, Alyna; Berk, Michael; et al.
Abstract Background Some degree of cognitive decline after surgery occurs in as many as one quarter of elderly surgical patients, and this decline is associated with increased morbidity and mortality. Cognition may be affected across a range of domains, including memory, psychomotor skills, and executive function. Whilst the exact mechanisms of cognitive change after surgery are not precisely known, oxidative stress and subsequent neuroinflammation have been implicated.N -acetylcysteine (NAC) acts via multiple interrelated mechanisms to influence oxidative homeostasis, neuronal transmission, and inflammation. NAC has been shown to reduce oxidative stress and inflammation in both human and animal models. There is clinical evidence to suggest that NAC may be beneficial in preventing the cognitive decline associated with both acute physiological insults and dementia-related disorders. To date, no trials have examined perioperative NAC as a potential moderator of postoperative cognitive changes in the noncardiac surgery setting. Methods and design This is a single-centre, randomised, double-blind, placebo-controlled clinical trial, with a between-group, repeated-measures, longitudinal design. The study will recruit 370 noncardiac surgical patients at the University Hospital Geelong, aged 60 years or older. Participants are randomly assigned to receive either NAC or placebo (1:1 ratio), and groups are stratified by age and surgery type. Participants undergo a series of neuropsychological tests prior to surgery, 7 days, 3 months, and 12 months post surgery. It is hypothesised that the perioperative administration of NAC will reduce the degree of postoperative cognitive changes at early and long-term follow-up, as measured by changes on individual measures of the neurocognitive battery, when compared with placebo. Serum samples are taken on the day of surgery and on day 2 post surgery to quantitate any changes in levels of biomarkers of inflammation and oxidative stress. Discussion The PANACEA trial aims to examine the potential efficacy of perioperative NAC to reduce the severity of postoperative cognitive dysfunction in an elderly, noncardiac surgery population. This is an entirely novel approach to the prevention of postoperative cognitive dysfunction and will have high impact and translatable outcomes if NAC is found to be beneficial. Trial registration The PANACEA trial has been registered with the Therapeutic Goods Administration, and the Australian New Zealand Clinical Trials Registry:ACTRN12614000411640 ; registered on 15 April 2014.